RECONCEPTUALIZING LEARNING MEDIA AS COGNITIVE–PEDAGOGICAL SYSTEMS: MULTIMODAL ENGAGEMENT OF GENERATION Z STUDENTS IN HEALTHCARE MARKETING EDUCATION - Jeki Purnomo; Irfan Kurniawan; Azharatul Jannah (Illea : Journal of Health Sciences, Public Health and Medicine, 2026)
Background: The increasing digitalization of higher education has positioned learning media as a central component of instructional design, particularly among Generation Z learners who exhibit strong multimodal and self-regulated learning behaviors. Despite widespread use of printed modules and presentation slides, limited research has examined how these media function as integrated cognitive systems within health administration education. Purpose: This study explores how Generation Z students interpret, use, and combine learning media formats (modules, slides, and blended use) within a Healthcare Marketing course, focusing on their role in shaping cognitive engagement, understanding, and learning strategies. Methods: A qualitative descriptive–interpretive design was implemented using in-depth interviews, optional focus groups, and document review. Data were analyzed through reflexive thematic analysis to identify patterns of media use, pedagogical meaning, and contextual interaction. Results: Students consistently positioned modules as the primary source of conceptual depth and academic reliability, while slides functioned as cognitive scaffolding tools that supported attention and comprehension during lectures. A dominant finding was the emergence of a sequential blended strategy, where students used slides during class and modules for post-class elaboration. Learning effectiveness was further mediated by environmental conditions and instructional delivery, indicating that media cannot be separated from context. Conclusion: Learning media in Generation Z cohorts operate as an integrated cognitive system rather than discrete tools, requiring alignment between media design, instructional delivery, and learning environment. This study contributes to instructional design literature by demonstrating that effective health education must move beyond single-media approaches toward structured multimodal integration grounded in cognitive and contextual realities.Abstrak diketik dengan dua Bahasa secara berurutan, yaitu Indonesia dan Inggris.